2020
DOI: 10.1021/acsnano.0c00180
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement by Ozone Treatment of 2D PdSe2

Abstract: Atomic-scale defects in two-dimensional transition metal dichalcogenides (TMDs) often dominate their physical and chemical properties. Introducing defects in a controllable manner can tailor properties of TMDs. For example, chalcogen atom defects in TMDs were reported to trigger phase transition, induce ferromagnetism, and drive superconductivity. However, reported strategies to induce chalcogen atom defects including postgrowth annealing, laser irradiation, or plasma usually require high temperature (such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 45 publications
6
56
1
1
Order By: Relevance
“…PbS QDs of the size ≈7 nm were synthesized as Ref. [ 63 ] . CuS NCs of the size ≈10 nm were synthesized by the method of Ref.…”
Section: Methodsmentioning
confidence: 99%
“…PbS QDs of the size ≈7 nm were synthesized as Ref. [ 63 ] . CuS NCs of the size ≈10 nm were synthesized by the method of Ref.…”
Section: Methodsmentioning
confidence: 99%
“…While defects in bulk semiconductors are usually considered as problematic, the defect engineering has been proved to be an effective pathway to introduce new functionalities in 2D semiconductors. [ 20,21 ] In several recent studies on BP oxidation, oxygen was reported to naturally dissociate in BP, inducing a reduction in BP layers. [ 22,23 ] According to density functional theory (DFT) calculation (Figure 1c), the incorporation of oxygen would induce in‐gap deep levels.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, one can selectively grow sub-stoichiometric MS x (1≤x<2), i.e., containing S vacancies, by regulating the growth parameters of low sulfur pressure and high temperature. In addition, the S-deficient defects can also be induced through the application of external forces, e.g., sonication, 48 laser irradiation, 49,50 plasma treatment 51 or thermal annealing in vacuum. 52…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%